Perancangan Protoype Kampung Digital Berbasis Microcontroller Esp-12 Dan Internet Of Things Menggunakan Vb.Net Sebagai Monitoring Dan Kendali - Abdul Halim Anshor; Pertiwi Dwi Ningsih (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Digital space has been proven by a large transformation in the information network and in global matters from any place in the world. Likewise the Internet of Things will connect every device that we might label as a smart device. Internet of things is one of the concepts that will be initiated in the research of Digital Village. The village government focuses efforts to advance the village that is advancing technologically. These villages can utilize the available resources in a smart and moderate way. The purpose of this research is to help improve the efficient use of electrical energy, increase the security level of villages and mosques from theft and anticipate fires caused by leakage of gas cylinders. The system development model used in this study is a prototyping model in which researchers create a software structure using the unified modeling method (UML) and hardware prototype design. The results of Prototype Design of Digital Kampung Based on Esp-12 Microcontroller and Internet of Things Using VB.Net as Monitoring and Control can be proven with RFID and PIR sensors that are able to send data to the microcontroller and forward it to digital village software, besides that digital village software also plays a role as a prototype controller. In this research, a security system and an early gas leak detection system have been successfully designed and successfully implemented. Keywords: Prototype, Microcontroller, Internet of Things, Monitoring.